Implementation Of Village Financial System In Village Financial Management - Sri Rahayu, Peti (Devotion : Journal of Research and Community Service, 2022)
In the government financial system in Indonesia, according to Law no. 6 of 2014, namely article 1 paragraph 1 which explains that the village is a legal community unit that has boundaries with the authorized area to regulate and manage government affairs and the interests of the local community based on community initiatives and rights and origins that are recognized and respected in a government system The Unitary State of the Republic of Indonesia. Villages are given such large financial resources by the central government with the aim that villages are able to improve the economy and the level of social welfare through these funds. To create clean, transparent, accountable, effective and efficient financial governance, the Financial and Development Supervisory Agency (BPKP) and the Directorate General of Village Government Development, the Ministry of Home Affairs, collaborated to create an application called the Village Financial System (Siskeudes). Human resources, leadership commitment are factors that can influence village financial management